LEGAL ASPECTS OF THE IMPLEMENTATION OF THE PROJECT "REMOTE CUSTOMS CONTROL - CUSTOMS WITHOUT A CUSTOMS OFFICER" AT INTERNATIONAL AIRPORTS OF UZBEKISTAN BASED ON THE RISK MANAGEMENT SYSTEM OF CUSTOMS AUTHORITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article describes the ways of improving the customs administration of the Republic of Uzbekistan, simplifying customs procedures, increasing the efficiency of the activities of customs authorities, the steps of introducing remote customs control at the international airports of the Republic of Uzbekistan on the example of the current regulatory legal documents. Examples of studying international experience in this field and statistical data on passengers are presented.